The legal status of intersex persons / edited by Jens M. Scherpe, Anatol Dutta, Tobias Helms. - Scherpe, Jens M., 1971-; Dutta, Anatol, 1976-; Helms, Tobias, 1978- (Intersentia, 2018)
The Legal Status of Intersex Persons provides a basis for discussion regarding all legal aspects concerning persons born with sex characteristics that do not belong strictly to male or female categories, or that belong to both at the same time. It contains contributions from medical, psychological and theological perspectives, as well as national legal perspectives from Germany, Australia, India, the Netherlands, Columbia, Sweden, France and the USA. It explores international human rights aspects of intersex legal recognition and also features chapters on private international law and legal history. The book is a timely one. Until very recently, the legal gender of a person - both at birth and later in life - in virtually all jurisdictions had to be recorded as either male or female; the laws simply did not allow any other option, and, in many cases, changing the recorded gender was difficult or impossible. However, there are many cases where this gender binary is unable to capture the reality of a person's physical presentation and/or perception of self. Consequently, this gender binary is increasingly being challenged and several jurisdictions have begun to reform their gender status laws. For example, in 2013 Germany became the first Western jurisdiction in modern times to introduce legislation allowing a person's gender to be recorded as 'indeterminate' at birth and thus give them a legal gender status other than male or female for all intents and purposes. However, this legislation has proved problematic in many ways and rightly was subject to pertinent criticism. In 2017 the German Constitutional Court then held that these rules were in violation of the German constitution as they only allowed a non-recognition, as opposed to a positive recognition of a gender other than male or female, and mandated law reform. Similarly, the Austria Constitutional Court held in June 2018 that current civil status laws had to be interpreted to allow registration of alternative gender identities. Therefore two European jurisdictions will now have legal gender recognition beyond the binary. This book looks at law reform taking place around the world, with diverse perspectives from relevant fields, to provide the reader with a comprehensive analysis of the legal status of intersex persons and related issues.